A case study on enhancing dairy cattle sustainability: The impact of silvopastoral systems and improved pastures on milk carbon footprint and farm economics in Cauca department, Colombia - Gonzalez Quintero, Ricardo; García, Elver Hernando; Florez, Fernando; Burkart, Stefan; Arango, Jacobo (Springer, 2024)
Cattle farming accounts for approximately 15% of Colombia’s greenhouse gas emissions (GHGE). Silvopastoral systems (SPS) and improved pastures (IP) are recognized as effective strategies for transforming dairy systems by enhancing cattle productivity, reducing climate change impact, and increasing farm profitability. This study aims to (i) calculate the carbon footprint (CF) of four small dairy cattle farms in the Cauca Department and (ii) identify improvements in milk yields, reductions in GHGE intensities after implementing SPS and IP, and changes in profitability indicators. GHGE were calculated using the 2019 Refinement to 2006 IPCC guidelines and impact factors from databases. Using a cradle-to-farm-gate approach, the functional units were one kg of fat and protein-corrected milk (FPCM) and one kg of live weight gain. A biophysical allocation method was applied to handling co-products leaving the farm. Baseline milk CFs ranged from 2.4 to 3.2 kgCO2–eq kgFPCM−1. In the improvement scenario, the area with SPS and IP covered more than 48% of the total farm area on average. SPS and IP increased the availability and quality of forage, leading to higher animal yields and reducing milk CF by up to 40% (ranging from 1.4 to 2.7 kgCO2–eq kgFPCM−1). These findings provide evidence of the positive impact of adopting IP and SPS on the sustainability of small dairy systems in Colombia by enhancing animal productivity and reducing GHGE intensities.